Misattributing the Source of Self-Generated Representations Related to Dissociative and Psychotic Symptoms - Chiu, Chui-De; Tseng, Mei-Chih Meg; Chien, Yi-Ling; Liao, Shih-Cheng; Liu, Chih-Min; Yeh, Yei-Yu; Hwu, Hai-Gwo (Frontiers in Psychology, 2016)
Objective: An intertwined relationship has been found between dissociative and psychotic symptoms, as the two symptom clusters frequently co-occur, suggesting some shared risk factors. Using a source monitoring paradigm, previous studies have shown that patients with schizophrenia made more errors in source monitoring, suggesting that a weakened sense of individuality may be associated with psychotic symptoms. However, no studies have verified a relationship between sense of individuality and dissociation, and it is unclear whether an altered sense of individuality is a shared sociocognitive deficit underlying both dissociation and psychosis. Method: Data from 80 acute psychiatric patients with unspecified mental disorders were analyzed to test the hypothesis that an altered sense of individuality underlies dissociation and psychosis. Behavioral tasks, including tests of intelligence and source monitoring, as well as interview schedules and self-report measures of dissociative and psychotic symptoms, general psychopathology, and trauma history, were administered. Results: Significant correlations of medium effect sizes indicated an association between errors attributing the source of self-generated items and positive psychotic symptoms and the absorption and amnesia measures of dissociation. The associations with dissociative measures remained significant after the effects of intelligence, general psychopathology, and trauma history were excluded. Moreover, the relationships between source misattribution and dissociative measures remained marginally significant and significant after controlling for positive and negative psychotic symptoms, respectively. Limitations: Self-reported measures were collected from a small sample, and most of the participants were receiving medications when tested, which may have influenced their cognitive performance. Conclusions: A tendency to misidentify the source of self-generated items characterized both dissociation and psychosis. An altered sense of individuality embedded in self-referential representations appears to be a common sociocognitive deficit of dissociation and psychosis.